Miss-allocation: The value of workplace gender composition and occupational segregation - Rachel Schuh (Federal Reserve Bank of New York, 2024)
I analyze the value workers ascribe to the gender composition of their workplace and the consequences of these valuations for occupational segregation, tipping, and welfare. To elicit these valuations, I survey 9,000 U.S. adults using a hypothetical job choice experiment. This reveals that on average women and men value gender diversity, but these average preferences mask substantial heterogeneity. Older female workers are more likely to value gender homophily. This suggests that gender norms and discrimination, which have declined over time, may help explain some women's desire for homophily. Using these results, I estimate a structural model of occupation choice to assess the influence of gender composition preferences on gender sorting and welfare. I find that workers' composition valuations are not large enough to create tipping points, but they do reduce female employment in male-dominated occupations substantially. Reducing segregation could improve welfare: making all occupations evenly gender balanced improves utility as much as a 0.4 percent wage increase for women and a 1 percent wage increase for men, on average
Keywords: J16; J24; J71; 330; gender; labor; occupation choice